Pengaruh Gaya Kepemimpinan Terhadap Kompensasi dan Loyalitas Karyawan di Jakarta Selatan - Buchori; Wulandari, Oryz Agnu Dian Wulandari; Ni Wayan F.A.L. (Awatara Publisher, 2025)
This study aims to analyze the influence of leadership style on employee compensation and loyalty in the South Jakarta area. An effective leadership style is believed to enhance employees’ perceptions of fairness and recognition, which in turn affects their loyalty to the organization. This research uses a quantitative approach with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The population of this study includes all employees working in private and service sectors in South Jakarta, with a sample of 100 respondents selected using purposive sampling. The analysis results indicate that leadership style has a positive and significant influence on compensation, with a t-statistic of 36.208 and a p-value of 0.000. Furthermore, leadership style significantly affects employee loyalty, as shown by a t-statistic of 7.848 and a p-value of 0.000. These findings suggest that leaders who apply effective leadership practices can create a fairer compensation system and strengthen employee loyalty. This research provides practical implications for human resource management to develop strategic, employee-centered leadership training programs.